2014
DOI: 10.1161/circheartfailure.114.001151
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Pressure-Overloaded and Infarcted Mouse Hearts

Abstract: Background Cardiac hypertrophy and heart failure are associated with metabolic dysregulation and a state of chronic energy deficiency. Although several disparate changes in individual metabolic pathways have been described, there has been no global assessment of metabolomic changes in hypertrophic and failing hearts in vivo. Here, we investigated the impact of pressure overload and infarction on myocardial metabolism. Methods and Results Male C57BL/6J mice were subjected to transverse aortic constriction (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
163
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(183 citation statements)
references
References 48 publications
15
163
3
2
Order By: Relevance
“…Although these metabolites represent a small portion of the human metabolome in terms of absolute numbers, they report on pathways critical for cellular and organism‐level homeostasis: fatty acid, carbohydrate, amino acid, and urea metabolism. These particular metabolites were chosen for several reasons: (1) An expanding body of evidence has implicated impairments in fatty acid and carbohydrate oxidation in HF pathophysiology, which could be reflected in acylcarnitine elevations13, 50, 73, 74, 75, 76, 77; (2) previous metabolomics investigations have identified derangements in plasma levels of these metabolites in HF patients49, 50, 78, 79, 80; and (3) acylcarnitines and their derivatives have been suggested to have intrinsic physiological effects that could contribute to the HF phenotype 66, 67, 68, 81, 82…”
Section: Discussionmentioning
confidence: 99%
“…Although these metabolites represent a small portion of the human metabolome in terms of absolute numbers, they report on pathways critical for cellular and organism‐level homeostasis: fatty acid, carbohydrate, amino acid, and urea metabolism. These particular metabolites were chosen for several reasons: (1) An expanding body of evidence has implicated impairments in fatty acid and carbohydrate oxidation in HF pathophysiology, which could be reflected in acylcarnitine elevations13, 50, 73, 74, 75, 76, 77; (2) previous metabolomics investigations have identified derangements in plasma levels of these metabolites in HF patients49, 50, 78, 79, 80; and (3) acylcarnitines and their derivatives have been suggested to have intrinsic physiological effects that could contribute to the HF phenotype 66, 67, 68, 81, 82…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation study found that only pyruvate was reduced in hearts under LV pressure overload. 27 In hamsters with dilated cardiomyopathy, it was reported that glucose-6-phosphate, fructose-6-phosphate, fructose-1, 6-bisphosphate, malate, iso-citrate, and succinate were comparable between the cardiomyopathy group and control group at 4 weeks of age, but were all reduced in the cardiomyopathy group at 16 weeks of age. 45 It is currently accepted that the alterations in glucose utilization vary according to the animal model, pathology, and stage of HF.…”
Section: Other Metabolitesmentioning
confidence: 97%
“…Levels of several sphingolipids are reported to be reduced in models of HF caused by LV pressure overload or myocardial infarction (MI). 27 Sphingosine-1-phosphate (S1P) is a bioactive cardioprotective sphingolipid that is more abundant in plasma than in the tissues and is mainly associated with high-density lipoprotein (50-60%) or albumin (30-40%). 28 S1P/S1P receptor 1 signaling was recently reported to contribute to Ca 2+ homeostasis by maintaining the Na + /H + exchanger 1 (NHE-1) in cardiomyocytes, thus having a cardioprotective effect in a myocardial ischemiareperfusion model.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to tissue collection, the mice were fasted for 16 h. After euthanasia, the adipose tissue was removed and immediately snap-frozen in liquid nitrogen. Relative metabolite abundance was then measured by GC/MS or LC/MS as described before (103,105).…”
Section: Introductionmentioning
confidence: 99%